KEABSAHAN PERJANJIAN KREDIT SECARA ONLINE BERBASIS FINANCIAL TECHNOLOGY DITINJAU DARI SEGI HUKUM - Wedaswara, Anak Agung Istri Anom Sinta; Rudy, Dewa Gde (Kertha Wicara : Journal Ilmu Hukum, 2022)
The following study aims to analyze and examine the validity and legal power of credit agreements conducted online based on financial technology (fintech), considering that now as the rapid sophistication of technology has brought all forms of convenience in various fields in the Country of Indonesia, including the financial industry. The reseacrh method used in this study is normative juridical with a statutory approach and concept approach. The results of the studies that have been conducted show that online credit agreements based on financial technology are valid as long as they meet the requirements stipulated in the KUHPer regarding of the validity of an agreement and because the agreement is valid it is binding and applies as a law for the parties who make it. Online credit agreements based on financial technology are included in the form of digital agreements, so the legal power of online credit agreements based on financial technology is strengthened by the existence of the Information and Technology Act. This online credit agreement is contained in a deed or electronic contract. Online credit has a fairly high risk, one form of risk that often occurs is bad credit. For this reason, it is necessary to strengthen the settlement mechanism in the event of bad credit. There are two efforts that can be taken if there is a bad credit problem, namely legal efforts and non-legal efforts, both can be taken based on the policy desired by the financial technology company itself.